Respiratory Syncytial Virus–Associated Hospital Admissions and Bed Days in Children <5 Years of Age in 7 European Countries. (12th January 2022) - Wang, Xin; Li, You; Vazquez Fernandez, Liliana; Teirlinck, Anne C; Lehtonen, Toni; van Wijhe, Maarten; Stona, Luca; Bangert, Mathieu; Reeves, Rachel M; Bøås, Håkon; van Boven, Michiel; Heikkinen, Terho; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of respiratory tract infections (RTIs) in young children. High-quality country-specific estimates of bed days and length of stay (LOS) show the population burden of RSV-RTI on secondary care services and the burden among patients, and can be used to inform RSV immunization implementation decisions. Methods: We estimated the hospital burden of RSV-associated RTI (RSV-RTI) in children under 5 years in 7 European countries (Finland, Denmark, Norway, Scotland, England, the Netherlands, and Italy) using routinely collected hospital databases during 2001–2018. We described RSV-RTI admission rates during the first year of life by birth month and assessed their correlation with RSV seasonality in 5 of the countries (except for England and Italy). We estimated average annual numbers and rates of bed days for RSV-RTI and other-pathogen RTI, as well as the hospital LOS. Results: We found that infants born 2 months before the peak month of RSV epidemics more frequently had the highest RSV-RTI hospital admission rate. RSV-RTI hospital episodes accounted for 9.9–21.2 bed days per 1000 children aged <5 years annually, with the median (interquartile range) LOS ranging from 2 days (0.5–4 days) to 4 days (2–6 days) between countries. Between 70% and 89% of these bed days were in infants aged <1 year, representing 40.3 (95% confidence interval [CI], 40.1–40.4) to 91.2 (95% CI, 90.6–91.8) bed days per 1000 infants annually. The number of bed days for RSV-RTI was higher than that for RTIs associated with other pathogens in infants aged <1 year, especially in those <6 months. Conclusions: RSV disease prevention therapies (monoclonal antibodies and maternal vaccines) for infants could help prevent a substantial number of bed days due to RSV-RTI. "High-risk" birth months should be considered when developing RSV immunization schedules. Variation in LOS between countries might reflect differences in hospital care practices. Abstract : Respiratory syncytial virus (RSV) disease prevention therapies (monoclonal antibodies and maternal vaccines) for infants could help prevent a substantial number of bed days due to RSV-associated respiratory tract infection. "High-risk" birth months should be considered when developing RSV immunization schedules.